2010
DOI: 10.1105/tpc.109.068478
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Role for Arabidopsis Mitochondrial ABC Transporter ATM3 in Molybdenum Cofactor Biosynthesis  

Abstract: The molybdenum cofactor (Moco) is a prosthetic group required by a number of enzymes, such as nitrate reductase, sulfite oxidase, xanthine dehydrogenase, and aldehyde oxidase. Its biosynthesis in eukaryotes can be divided into four steps, of which the last three are proposed to occur in the cytosol. Here, we report that the mitochondrial ABC transporter ATM3, previously implicated in the maturation of extramitochondrial iron-sulfur proteins, has a crucial role also in Moco biosynthesis. In ATM3 insertion mutan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
121
0
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 125 publications
(131 citation statements)
references
References 62 publications
(86 reference statements)
7
121
0
1
Order By: Relevance
“…Loss of ATM3 function is associated not only with a deficiency in extramitochondrial Fe-S proteins but also with an accumulation of cPMP in mitochondria, which has the consequence that the cytosol becomes short of cPMP, thus leading to decreased Moco levels and molybdenum enzyme activities in the cell (36). The precise role of ATM3 is still unknown, however.…”
Section: Figure 3 Organization Of Biosynthesis and Distribution Of Mmentioning
confidence: 99%
See 2 more Smart Citations
“…Loss of ATM3 function is associated not only with a deficiency in extramitochondrial Fe-S proteins but also with an accumulation of cPMP in mitochondria, which has the consequence that the cytosol becomes short of cPMP, thus leading to decreased Moco levels and molybdenum enzyme activities in the cell (36). The precise role of ATM3 is still unknown, however.…”
Section: Figure 3 Organization Of Biosynthesis and Distribution Of Mmentioning
confidence: 99%
“…3). Although cPMP is hydrophobic enough to pass through biological membranes simply by diffusion, recent work on plants demonstrated that a specific transporter in the inner membrane of mitochondria is involved in the transport of cPMP into the cytosol (36). The respective transporter belongs to the ABC transporter family and is referred to as ATM3 in plants.…”
Section: Export Of Cpmp From Mitochondria and A Link Between Moco Andmentioning
confidence: 99%
See 1 more Smart Citation
“…The reaction assay contained 0.1 M Tris-HCl buffer, pH 8.48, 0.1 mM Na 2 SO 3 , 5 mM b-mercaptoethanol, 50 mM NaSCN, and 80 mg mL 21 desalted protein extract treated before the assay with 1 mM tungstate for 30 min at 4°C to disrupt SO activity that consumes sulfite. The sulfite-consuming activity was measured during 15 min at 37°C and was estimated as sulfite disappearance, as described for SO activity (Pachmayr, 1960;Lang et al, 2007;Khan et al, 2010;Teschner et al, 2010;Brychkova et al, 2012a) and employing Na 2 SO 3 as a standard in solution containing NaSCN. Sulfite-consuming activity was assayed also as SCN 2 disappearance by detecting Fe(SCN) 3 (Papenbrock and Schmidt, 2000a).…”
Section: St Kinetic Activitymentioning
confidence: 99%
“…In brief, SO activity was measured as the disappearance of sulfite (Pachmayr, 1960;Lang et al, 2007;Khan et al, 2010;Teschner et al, 2010;Brychkova et al, 2012a). The desalted protein extracts were treated with 1 mM tungstate for 30 min at 4°C to inhibit SO activity (Brychkova et al, 2012a).…”
Section: Protein Extraction and Kinetic Assays For So Apr And Sir Amentioning
confidence: 99%